Project crashing in construction industry: investigation of the strategies, challenges and impacts - Muhammad Redho, Mardzuki (2013)
This survey is conducted to study the project crashing in the aspect of the strategies and challenges in construction industry. Besides, this study also identified the impacts on cost, time and quality once the strategies are being implemented. The objectives of this study were to identify the strategies that can crash a project successfully, to identify the challenges in project crashing and to examine the relationship between the strategies used in project crashing and the impacts in terms of cost, time and quality. The data are obtained mainly from the primary data which is the survey questionnaires. Total sample of 54 respondents were used in this study. The result of this study has identified the suitable strategies to crash a project, the challenges faced in project crashing and also see the impact of the strategies used in terms of cost, time and quality.